Reseñas - Pautasso, Alejandro; Mazzini Puga, Lautaro; Cardozo, Daniel Carlos; Kan, Julián; Ablin, Silvana; Benassai, Paola; Verdo, Geneviève (Boletín del Instituto de Historia Argentina y Americana Dr. Emilio Ravignani, 2023)
Alejandro Pautasso, Lautaro Mazzini Puga, Daniel Carlos Cardozo, Julián Kan, Silvana Ablin, Paola Benassai, Geneviève Verdo.